A gallery of the Templeton Laureates from 1973-2018, including Holmes Rolston - Templeton Foundation, photographer (Colorado State University. Libraries, 2018)
Poster featuring the Templeton Laureates from 1973-2018.

To read the names of the individual prizewinners, enlarge to 300% or click on Zoom + to enlarge poster as desired.
To read the names of the individual prizewinners, enlarge to 300%.
Keywords: Templeton laureates; Rolston, Holmes, 1932-2025